The Inherited Intestinal Microbiota from Myeloid-Specific ZIP8KO Mice Impairs Pulmonary Host Defense against Pneumococcal Pneumonia - Derrick R. Samuelson; Deandra R. Smith; Kelly C. Cunningham; Sabah Haq; Daniel N. Villageliú; Christi M. Ellis; Niaz Bahar Chowdhury; Amanda E. Ramer-Tait; Jeffrey D. Price; Daren L. Knoell (Pathogens, 2023)
Intestinal dysbiosis increases susceptibility to infection through the alteration of metabolic profiles, which increases morbidity. Zinc (Zn) homeostasis in mammals is tightly regulated by 24 Zn transporters. ZIP8 is unique in that it is required by myeloid cells to maintain proper host defense against bacterial pneumonia. In addition, a frequently occurring ZIP8 defective variant (SLC39A8 rs13107325) is strongly associated with inflammation-based disorders and bacterial infection. In this study, we developed a novel model to study the effects of ZIP8-mediated intestinal dysbiosis on pulmonary host defense independent of the genetic effects. Cecal microbial communities from a myeloid-specific Zip8 knockout mouse model were transplanted into germ-free mice. Conventionalized ZIP8KO-microbiota mice were then bred to produce F1 and F2 generations of ZIP8KO-microbiota mice. F1 ZIP8KO-microbiota mice were also infected with S. pneumoniae, and pulmonary host defense was assessed. Strikingly, the instillation of pneumococcus into the lung of F1 ZIP8KO-microbiota mice resulted in a significant increase in weight loss, inflammation, and mortality when compared to F1 wild-type (WT)-microbiota recipients. Similar defects in pulmonary host defense were observed in both genders, although consistently greater in females. From these results, we conclude that myeloid Zn homeostasis is not only critical for myeloid function but also plays a significant role in the maintenance and control of gut microbiota composition. Further, these data demonstrate that the intestinal microbiota, independent of host genetics, play a critical role in governing host defense in the lung against infection. Finally, these data strongly support future microbiome-based interventional studies, given the high incidence of zinc deficiency and the rs13107325 allele in humans.